Kinetics of individual grains during recrystallization of cold-rolled copper. Issue 1 (April 2015) - Lin, F X; Zhang, Y B; Poulsen, S O; Schell, N; Pantleon, W; Jensen, D Juul
Abstract: The formation of a recrystallization texture is closely related to the nucleation and growth of recrystallizing grains, which may vary from grain to grain. Cube texture is a commonly observed recrystallization texture in face centered cubic metals of medium to high stacking fault energy after heavy cold-rolling and annealing. In this work, recrystallization of pure copper cold-rolled to a von Mises strain of 2.7 was investigated in situ using three-dimensional X-ray diffraction. Growth curves of 835 grains were determined, and the curves of cube and noncube grains were compared. It was found that the nucleation times of cube grains and non-cube grains were similar, whereas the growth rates of a few but not all cube grains were high. Effects hereof for the development of the cube texture were discussed.